Metastatic Bone Disease: A Clinical Approach - Dim, Edwin Maduakonam; He, Zu Sheng; Liu, De Fu (Journal of Southeast Asian Orthopaedics, 2025)
Background: Advances in oncological management have contributed to longer survival of patients, even in the presence of metastases. Consequently, more patients would be expected to present with symptomatic bony metastases. The major objectives of orthopaedic surgical interventions in bone metastases include stabilization of impending or actual pathological fractures, restoration of mobility and gait, with resultant reduction in the overall morbidity during the survival period of the cancer patient. Purpose: This review was aimed at producing a synoptic material for ease of reference by students, trainees and young surgeons who come into contact with patients suffering from metastatic bone lesions. Methods: A review of the literature on the subject of metastatic bone diseases was done. Information on epidemiology, pathophysiology and mechanisms of bone metastases, clinical problems and concept of skeletal related events (SREs), differential diagnoses, diagnostic approach, general principles and options of treatment, and prognosis was extracted and presented. Conclusions: Metastatic lesions are the most common malignant tumours that affect the skeleton, and these malignant deposits in bones increase overall morbidity in cancer patients. Appendicular skeleton offers a large surface area for deposition of tumour cells from primary sites, including the breast, prostate, lung, kidney and thyroid, with the highest incidence coming from breast and prostate. The osseous lesions of primary malignant diseases predispose to pain, mechanical instability and fractures in the affected parts. These factors contribute to the overall morbidity and reduced survival in cancer patients.